Medicinal Plants Used by the Inhabitants of Alfred Nzo District Municipality in the Eastern Cape Province, South Africa - Zingisa Thinyane; Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2019)
Plant species used as herbal medicines play an important in the provision of primary healthcare in several rural communities. The current study was aimed at documenting medicinal plants used by the inhabitants of Alfred Nzo District Municipality in the Eastern Cape province, South Africa. Information on medicinal plants used for primary healthcare was collected through open-ended interviews with a sample of 124 participants selected via snowball-sampling technique between April 2017 and May 2018. A total of 34 plant species and one fungus species representing 20 families were used in the treatment of 13 different human diseases. The major diseases treated by the documented species included respiratory system, pain, sores and wounds, infections and infestations, digestive system, blood and cardiovascular system, fever and malaria, general ailments, reproductive system and sexual health and mental disorders. Popular herbal medicines with relative frequency citation (RFC) values exceeding 0.50 included Bulbine frutescens, Clivia miniata var. miniata, Elephantorrhiza elephantina, Centella asiatica, Hypoxis hemerocallidea, Dicerothamnus rhinocerotis, Leonotis leonurus, Agapanthus africanus and Datura stramonium. Such repository of medicinal plants and fungi reinforces the need for an evaluation of their biological activities as a basis for developing future medicines and pharmaceutical products.